PBL Berbantu Multimedia Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Sekolah Dasar - Lia Harum Sari; Mawardi Mawardi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
Education is a basic need for human life and in Indonesia, every citizen has equal rights with one. This study aims to improve students' critical thinking skills by applying multimedia-assisted Problem Based Learning (PBL). This research is a classroom action research with the Stringer model, which consists of looking, thinking and acting. The research subjects were third-grade students of SDN 2 Krapyak, conducted in the second semester of the 2021/2022 academic year. Data collection techniques using test and non-test techniques. The data analysis technique used percentage and category techniques. Based on the results of research on the Critical Thinking Ability of Class III Students using the PBL model assisted by multimedia, it can be concluded that: 1) The critical thinking ability of students has increased as evidenced by the very high category difference in cycles 1 and 2, namely 7.15%. (2) The average student learning outcomes have increased, as evidenced by the difference in the very high category in cycles 1 and 2, namely 14.29%.